A rare cause of lower gastrointestinal bleeding treated with robotic colorectal surgery - Robin Osofsky; Cyril Kamya; Hamza Hanif; Victor Phuoc (Surgical Case Reports, 2021)
Abstract Background Metastatic melanoma to the colon is rarely diagnosed with an incidence of only 0.3% and more than 95% of cases identified post-mortem. Survival for patients with metastatic melanoma to the colon is poor, with 5-year survival rates of 26.5%. Nonetheless, surgical resection of the colonic metastatic melanoma lesions is recommended as it is associated with improved survival. Additionally, surgical resection is also indicated for palliative reasons, as symptom resolution is achieved in 90% of such patients. Use of the surgical robot has increased dramatically in the past decades, especially in the field of colorectal surgery. Furthermore, recent studies have demonstrated comparable outcomes between patients undergoing either laparoscopic or robotic-assisted colorectal surgery for cancer. Here, we describe the first case, to the authors knowledge, of a robot-assisted sigmoid colectomy for metastatic melanoma. Case presentation A 72-year-old male with a history of metastatic melanoma diagnosed in 2015 with a favorable response to immunotherapy presented to the emergency department with symptomatic lower gastrointestinal bleeding (LGIB). Endoscopy demonstrated a friable melanotic lesion of the sigmoid colon with biopsy demonstrating histopathologic evidence of metastatic melanoma. After further evaluation, the patient consented for an elective robot-assisted segmental colectomy for palliative intent. Diagnostic laparoscopy identified no evidence of further intra-abdominal metastatic disease. After identifying the metastatic lesion in the sigmoid colon, the mesentery of involved segment of sigmoid colon adjacent to the lesion was divided using the bipolar electrosurgical vessel sealer device. The colon was divided both proximal and distal to the lesion using a robotic stapler and a tension-free colo-colonic anastomosis was created intracorporeally. Postoperatively, the patient had an unremarkable course and was discharged home on post-operative day 3. On follow-up, the patient was doing well with resolution of preoperative LGIB. Conclusion  This case highlights a rare presentation of metastatic melanoma to the colon in a patient presenting with LGIB. Furthermore, this case demonstrates the feasibility of the minimally invasive robotic-assisted approach for an uncommon pathology.